(untitled) (Marketing Journal, 2026)
Abstract The article reveals the prospects for attracting foreign and domestic investments in order to implement the tasks set out in the development strategy of Uzbekistan, increase the effectiveness of measures taken to ensure “green” and inclusive economic growth within the framework of the strategy of transition of the Republic of Uzbekistan to a “green” economy, further expand the use of renewable energy sources, and save resources in all sectors of the economy. Keywords: green economy, green investment, green energy, foreign investors, green financing.